Edible Plants : A Photographic Survey of the Wild Edible Botanicals of North America - Fike, Jimmy W. (Book collections on Project MUSE., 2021)
"Featuring over 100 photographs that Fike has selectively colorized to highlight the comestible part of the plant. While the images initially appear to be scientific illustrations or photograms from the dawn of photography when plants were placed directly on sensitized paper and exposed under the sun, a closer look reveals, according to Liesl Bradner of the Los Angeles Times, "haunting [and] eerily beautiful" photographs. Beyond instilling wonder, Fike's contemporary, place-based approach to landscape photography emphasizes our relationship to the natural world, reveals food sources, and encourages environmental stewardship. His clever and beautiful method makes it easy to identify both the specimen and its edible parts and includes detailed descriptions about the plant's wider purposes as food and medicine. Sumptuously illustrated and delightfully informative, Edible Plants is the perfect gift for anyone curious about unlocking the secrets of native North American plants"--